The Concept of the Soul (Tazkiyatun Nafs) and Its Influence in the View of the Qur'an Surah al-Shams - Muthoifin, Muthoifin; Lestari, Putri Dwi (Prosiding University Research Colloquium, 2022)
The purpose of this study is to reveal the conception and meaning of the soul (tazkiyatun nafs) who always worships Allah and to find out what things can make humans lucky and harmed. This research is a type of qualitative research. The research technique is by collecting data related to the problem being studied, library research or library research, where data is collected from several literatures such as books, magazines, articles and other writings and conclusions can be drawn based on the theory taken. The result of the research is that humans are essentially able to understand and understand the meaning of a healthy soul, a sick soul, and a dead soul. Humans know that the practice is carried out in accordance with what is intended in the heart and know about the cleanliness of the soul or tazkiyatun nafs contained in the letter al-Syamsy. The purpose of humans being created is to worship, humans were created in a perfect form than other creatures, therefore humans have the advantage of having two dimensions of the soul that are very influential in human life itself. The first dimension is material (madah) which in a philosophical sense is also called the animal dimension, meaning that humans are created in a position between animals and angels which contain animal traits, angels, and so on. The second is the spiritual dimension which in terms of philosophy is called the spirit (nafs). Humans are the most noble creatures. Therefore, there is a need for purification of the soul (tazkiyatun nafs) in human life so that our souls are calm and clean from immoral things.